The Wedding Complex : Forms of Belonging in Modern American Culture - Freeman, Elizabeth, 1966- (Book collections on Project MUSE., 2002)
A queer literary and cultural studies examination of the wedding ceremony (rather than the resulting marriages) which finds it to be a space of more open possibilities than might normally be supposed.